ANALYSIS OF USER SATISFACTION ON VIDIO APPLICATIONS USING A COMBINATION OF TECHNOLOGY ACCEPTANCE MODEL (TAM) AND FRAMEWORK PIECES: ANALISIS KEPUASAN PENGGUNA PADA APLIKASI VIDIO MENGGUNAKAN KOMBINASI METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN PIECES FRAMEWORK - Istiqomah, Nurul -; Nuryana, I Kadek Dwi (Universitas Negeri Surabaya, 2023)
The development of film technology has also encouraged cinema to develop even more broadly with the presence of video streaming platforms which are now increasing, even involving entertainment industry players. Platform names such as Netflix, Video.com, Hooq, and Amazon Prime are certainly no strangers to movie lovers. The Vidio application is a video-sharing application founded by Adi Sariatmadja in October 2014 and managed by PT Kreatif Media Karya, a subsidiary of Emtek. The Vidio application allows users to upload, watch and share videos. The Vidio application has more than 50 million users on the PlayStore with a rating of 3.9/5.0 and 499 thousand reviews. With the several advantages provided by the Vidio Application, there are still problems that often occur such as a limited choice of films, especially the latest films, some find some films with slow sound and are rather difficult to watch on a cellphone. These problems will affect user satisfaction. This study uses the Technology Acceptance Model (TAM) and Pieces Framework methods to determine user satisfaction with the Vidio application. The factors discussed in the TAM method include Perceived usefulness, Perceived Ease of Use. While the factors used in the Pieces Framework method include Performances, Information and Data, Economics, Control and Security, Efficiency, and Service. Data collection was carried out by distributing questionnaires to 100 people. Based on the data analysis that was carried out using the SmartPLS software, it was found that 93.75% of the Vidio application users were in the very satisfied category.